Segregation Effect on Solidification Cracking in Spot Welding of the 6XXX Aluminum - RAMIREZ, Andrés; GRACIANO-URIBE, Jonathan; HINCAPIE ZULUGA, Diego; TORREZ LOPEZ, Edwar (Engineering Transactions, 2020)
Solidification cracking is a critical phenomenon, especially in the welding of AA6XXX, due these alloys present a wider freezing temperature range. The amount of liquid at the end of the solidification is a dominant factor in promoting or reducing the number of cracks. This paper proposes to assess the effect of the heat input in controlling the cracking during the spot welding in AA6061-T6. Four deposit conditions, made with GTAW, were assessed, in which the cracking degree was quantified and compared with the resulting microstructure. This work confirms and explains why the heat input governs the constitutional cooling, which simultaneously controls the microsegregation amount. With low heat input, the segregation is interdendritic, and the eutectic liquid gathers within the grains, which reduces the cracking susceptibility. A high heat input promotes the higher accumulation of eutectic liquid at the grain boundaries, facilitating cracks’ formation and growth. A high concentration of eutectic liquid promotes the healing effect, reducing the formation of cracks.